Correction: Analysis of long dsRNA produced in vitro and in vivo using atomic force microscopy in conjunction with ion-pair reverse-phase HPLC. Issue 22 (16th October 2019) - Nwokeoji, Alison O.; Kumar, Sandip; Kilby, Peter M.; Portwood, David E.; Hobbs, Jamie K.; Dickman, Mark J.
Abstract : Correction for 'Analysis of long dsRNA produced in vitro and in vivo using atomic force microscopy in conjunction with ion-pair reverse-phase HPLC' by Alison O. Nwokeoji, et al., Analyst, 2019, 144, 4985–4994.